SEJARAH PEMBANGUNAN TEKNOLOGI KETENTERAAN KERAJAAN BANU MARIN DI AL-MAGHRIB (History of Military Technology Development of the Marinid Kingdom in the Maghreb) - Ashari, Mohamad Zulfazdlee Abul Hassan; Jamsari, Ezad Azraai; Safian, Nursafira Lubis; Safiai, Mohd Hafiz (Journal of Al-Tamaddun, 2020)
The Marinid Kingdom (1215-1465CE) was a Muslim Sultanate which once ruled the Maghreb in the medieval centuries. It succeeded the Muslim leadership of Almohad Caliphate, and was considered as strong and stable when it dominated the entire Maghreb during its golden age. Among the driving factors for Marinid glory was its military prowess. The purpose of this article is to examine the history of Marinid ground military power through retrospective analysis, particularly in the aspect of military technology relating to armaments (weaponry technology and military equipment). The whole of this research used qualitative methodology in data collection and analysis, and was designed to apply historical study and content analysis methods. Documentation method was used in data collection, focusing on some primary and secondary sources. Using a descriptive approach, data was analysed by internal and external critique methods. Research findings conclude that the Marinid Kingdom empowered its ground military system by increasing the capability of its armament and equipment technology. The Marinid ruler’s support and available expertise in society invigorated the development of ground military technology and production of ground military armament. The know-how to produce its own military armament put new strength in Marinid military prowess, at once contributing to the political stability of the Marinid Kingdom in the Maghreb region.